2019
DOI: 10.1016/j.bjorl.2018.04.013
|View full text |Cite
|
Sign up to set email alerts
|

The evaluation of pretreatment neutrophil–lymphocyte ratio and derived neutrophil–lymphocyte ratio in patients with laryngeal neoplasms

Abstract: Pretreatment neutrophil-lymphocyte ratio is a useful and reliable predictive and prognostic biomarker for patients with laryngeal carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 37 publications
0
15
0
3
Order By: Relevance
“…Its 5-year survival rate is approximately 75% in patients with localized disease, 44% in patients with regional disease, and 35% in patients with distant disease. 1 When there is regional or distant metastasis, the 5-year survival rate drops significantly. Laryngeal squamous cell carcinoma accounts for 85% to 95% of all laryngeal carcinomas, and the age of onset for this disease is now earlier than it was in the past.…”
Section: Introductionmentioning
confidence: 99%
“…Its 5-year survival rate is approximately 75% in patients with localized disease, 44% in patients with regional disease, and 35% in patients with distant disease. 1 When there is regional or distant metastasis, the 5-year survival rate drops significantly. Laryngeal squamous cell carcinoma accounts for 85% to 95% of all laryngeal carcinomas, and the age of onset for this disease is now earlier than it was in the past.…”
Section: Introductionmentioning
confidence: 99%
“…20,21 However, there are a few studies with different results evaluating the usability of NLR for the differentiation of BG, PG and MG in laryngeal lesions. 10,11,[22][23][24][25] In the present study, it was found that NLR in MG laryngeal was statistically higher than BG laryngeal lesions. However, in PG lesions, NLR was not different from BG and MG groups.…”
Section: Discussionmentioning
confidence: 73%
“…Bu ilişkiden dolayı lenfosit düzeyi ile hastalığın ciddiyeti korelasyon göstermektedir. 16 Damar ve ark., Cheng ve ark., Kawakita ve ark., Seng ve ark., ile Kuzucu ve ark.nın yaptıkları çalışmalarda, NLR ve PLR'yu malign lezyonlarda daha yüksek olarak saptanmıştır. 1,15,[17][18][19] Malign parotis tümörlü hastalarda, benign parotis tümörlü hastalara göre yüksek NLR, yüksek nötrofil yüzdesi, düşük lenfosit sayısı ve düşük lenfosit yüzdesi saptanmıştır.…”
Section: Bulgularunclassified